Authentic communication : Christian speech engaging culture - Muehlhoff, Tim, 1961-; Lewis, Todd Vernon, 1949- (Downers Grove, Ill. : IVP Academic, 2010)
Whether setting about to love our neighbor, to settle a dispute, to share in the suffering of others or to speak up on behalf of the marginalized, we inevitably must engage in communication. And what could be more natural, more human, than communication? But we all learn quickly enough that good communication is not always natural. There is much to learn from Scripture and from the academic study of human communication. Tim Muehlhoff and Todd Lewis are able guides, aiding us in understanding the broad field of human communication in Christian perspective. Here they offer readers a vital assessment of the power of words, perspective-taking, persuasion and conflict management--all in an effort to improve our abilities to communicate forgiveness and shape the world we live in for the good. Special attention is focused on the place of Christians as counterpublics--those who offer alternative perspectives to the dominant voices in society. - Publisher.
Introduction -- pt. 1. Understanding the components of communication. The power of human communication -- Perspective taking : engaging the views of others -- Words! words! words! : we can only imagine -- Persuasion : spiritual power or manipulation and rhetorical tricks -- pt. 2. Applying communication. Before the sun sets : conflict and Christian unity -- Communicating forgiveness -- Communicating about and evaluating the messages of popular culture -- Resident aliens : Christians as counterpublics -- Postmodern times and Christian counterpublics, part 1 -- Postmodern times and Christian counterpublics, part 2 -- Abnormal communication : a Christian response to the argument culture -- Social justice : speaking for the marginalized.
Includes bibliographical references and index.
Keywords: Communication -- Religious aspects -- Christianity; Christianity and culture